2022
DOI: 10.1523/jneurosci.1160-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Inflammatory Agent Bindarit Attenuates the Impairment of Neural Development through Suppression of Microglial Activation in a Neonatal Hydrocephalus Mouse Model

Abstract: Neonatal hydrocephalus presents with various degrees of neuroinflammation and long-term neurologic deficits in surgically treated patients, provoking a need for additional medical treatment. We previously reported elevated neuroinflammation and severe periventricular white matter damage in the progressive hydrocephalus (prh) mutant which contains a point mutation in the Ccdc39 gene, causing loss of cilia-mediated unidirectional CSF flow. In this study, we identified cortical neuropil maturation defects such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
16
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 140 publications
7
16
1
Order By: Relevance
“…Improvement in muscle regeneration was not observed in adult mice, despite the presence of fewer circulatory monocytes (Figure S12A-F). It was also not detrimental, possibly bene ting from circumstances with chronic in ammation only, as previously reported [52][53][54] .…”
Section: Epigenetic Erosion Of H4k20 Drives Musc Population Drift Tow...supporting
confidence: 77%
“…Improvement in muscle regeneration was not observed in adult mice, despite the presence of fewer circulatory monocytes (Figure S12A-F). It was also not detrimental, possibly bene ting from circumstances with chronic in ammation only, as previously reported [52][53][54] .…”
Section: Epigenetic Erosion Of H4k20 Drives Musc Population Drift Tow...supporting
confidence: 77%
“…To test the effects of CCL2 upon initiation of HIV brain disease by an alternate approach, we employed the compound bindarit that inhibits transcription of CCL2 through interference with NFÎșB activation at the CCL2 promoter 35 . In mice, bindarit blocks expression of CCL2 RNA and protein and prevents inflammatory monocyte entry into the brain 46 and it also prevents pathological microglia activation during impaired neonatal brain development 47 . C57BL/6 mice were pretreated with bindarit 1 day before EcoHIV infection by IP injection and then treated daily through RAWM testing starting on Day 25 until euthanasia on Day 32 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The mutation also causes periventricular white matter injury and neuroinflammation. Iwasawa et al [ 126 ] found that an anti-inflammatory agent, Bindarit, improved cortical development and reduced white matter injury in these mice while having only a mild effect on ventricular volume.…”
Section: Neurological Disordersmentioning
confidence: 99%